Transcriptional regulation of BRCA1 expression by a metabolic switch - Di, Li Jun (2010)
Though the linkages between germline mutations of BRCA1 and hereditary breast cancer are well known, recent evidence suggests that altered BRCA1 transcription may also contribute to sporadic forms of breast cancer. Here we show that BRCA1 expression is controlled by a dynamic equilibrium between transcriptional coactivators and co-repressors that govern histone acetylation and DNA accessibility at the BRCA1 promoter. Eviction of the transcriptional co-repressor and metabolic sensor, C terminalgbinding protein (CtBP), has a central role in this regulation. Loss of CtBP from the BRCA1 promoter through estrogen induction, depletion by RNA interference or increased NAD + /NADH ratio leads to HDAC1 dismissal, elevated histone acetylation and increased BRCA1 transcription. The active control of chromatin marks, DNA accessibility and gene expression at the BRCA1 promoter by this 'metabolic switch' provides an important molecular link between caloric intake and tumor suppressor expression in mammary cells. © 2010 Nature America, Inc. All rights reserved.